Tolerance and efficacy of targeted therapies prescribed for off-label indications in refractory systemic autoimmune diseases: data of the first 100 patients enrolled in the TATA registry (TArgeted Therapy in Autoimmune Diseases). Issue 2 (1st November 2022) - Gottenberg, Jacques-Eric; Chaudier, Aurore; Allenbach, Yves; Mekinian, Arsène; Amoura, Zahir; Cacoub, Patrice; Cornec, Divi; Hachulla, Eric; Quartier, Pierre; Melki, Isabelle; Richez, Christophe; Seror, Raphaele; et al.
Abstract : Objectives: To assess the tolerance and efficacy of targeted therapies prescribed off-label in refractory low-prevalence autoimmune and inflammatory systemic diseases. Methods: The TATA registry (TArgeted Therapy in Autoimmune Diseases) is a prospective, observational, national and independent cohort follow-up. The inclusion criteria in the registry are as follows: age >18 years; low-prevalence autoimmune and inflammatory systemic disease treated with off-label drugs started after 1 January 2019. Results: Hundred (100) patients (79 women) were enrolled. The median age was 52.5 years (95% CI 49 to 56) and the median disease duration before enrolment was 5 years (3 to 7). The targeted therapies at enrolment were as follows: Janus kinase/signal transducers and activators of transcription inhibitors (44%), anti-interleukin (IL)-6R (22%), anti-IL-12/23, anti-IL-23 and anti-IL-17 (9%), anti-B cell activating factor of the tumour necrosis factor family (5%), abatacept (5%), other targeted treatments (9%) and combination of targeted treatments (6%). 73% of patients were receiving corticosteroid therapy at enrolment (median dose 10 mg/day). The current median follow-up time is 9 months (8 to 10). Safety: 11 serious infections (incidence rate of 14.8/100 patient-years) and 1 cancer (1.3 cancers/100 patient-years) were observed. Two patients died from severe COVID-19 (2.7 deaths/100 patient-years). Efficacy: the targeted treatment was considered effective by the clinician in 56% of patients and allowed, in responders, a median reduction of oral corticosteroids of 15 (9 to 21) mg/day, below 7.5 mg/day in 76% of patients, while 28% discontinued. Conclusion: These initial results of the TATA registry confirm the diversity of targeted treatments prescribed off-label in refractory autoimmune diseases and their corticosteroid-sparing effect when effective. Tolerance was acceptable in these refractory patients with a long history of treatment with immunosuppressive drugs.